A remote PDP-8 interface. - Goyette, Pierre. (University of Ottawa (Canada), 1968)
This thesis deals with the design and construction of a communication system for a digital equipment corporation PDP-8 digital computer. The thesis first shows the general operation of the computer and the specifications of the required system and then proceeds to study various possible designs which could meet the specifications. The designs are compared and the one considered best chosen. This chosen design is further developed and its implementation using integrated circuits is shown in detail. The design of the system is discussed as a function of the various tasks that the subsystems must accomplish.
Keywords: Engineering, Electronics and Electrical.